Blackhat [videorecording (DVD)] - Hemsworth, Chris; Davis, Viola, 1965-; Tang, Wei, 1979- (Universal Studios Home Entertainment, 2015)
A furloughed convict and his American and Chinese partners hunt a high-level cybercrime network from Chicago to Los Angeles to Hong Kong to Jakarta.